2014
DOI: 10.1155/2014/607528
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Factors on the Carbon Dynamics at Hooghly Estuarine Region

Abstract: Degradation of litter from mangrove forests adjacent to the creeks at Sagar Island of the Hooghly-Matla estuarine ecosystem is one of the principal sources of nutrient to the estuary. This system receives a major load of carbon from adjacent mangrove forest in the form of litterfall throughout the year. Keeping in view, the effect of environmental factor on the dynamics of carbon is studied through multivariate statistics. Essential environmental variables like soil carbon, dissolved carbon, temperature, salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…The principal component analysis, which was performed to set a well-defined distinction between environmental parameters and stations, revealed significant correlation for St-4 and St-5 with environmental parameters such as temperature, salinity, pH, saturation, wind speed, DO, alkalinity, CO3, DOC and sand, while stations St-1, St-2 and St-3 showed significant correlation with other environmental parameters. Similar variables' combinations were observed earlier by Medeiros et al [68] in eastern Canadian Arctic; Mukherjee et al [69] in Hooghly estuarine region; and Sigamani et al [50] in Vellar-Coleroon estuarine system.…”
Section: Discussionsupporting
confidence: 84%
“…The principal component analysis, which was performed to set a well-defined distinction between environmental parameters and stations, revealed significant correlation for St-4 and St-5 with environmental parameters such as temperature, salinity, pH, saturation, wind speed, DO, alkalinity, CO3, DOC and sand, while stations St-1, St-2 and St-3 showed significant correlation with other environmental parameters. Similar variables' combinations were observed earlier by Medeiros et al [68] in eastern Canadian Arctic; Mukherjee et al [69] in Hooghly estuarine region; and Sigamani et al [50] in Vellar-Coleroon estuarine system.…”
Section: Discussionsupporting
confidence: 84%
“…The low availability of DO may lower the activity of microbes and detritivores and could be the reason for slightly lowered TIC values observed during the monsoon season. The low TIC values during the monsoon season due to variation in microbial activity were also previously reported in other Indian mangrove habitats (Mukherjee et al., 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Mukherjee et al. (2014) suggested that an increase in DIC during pre‐monsoon is likely due to high community respiration. All these lines of evidence indicate that although mangrove ecosystems are net autotrophic, their water and sediments remain net heterotrophic due to the high OM turnover.…”
Section: Discussionmentioning
confidence: 99%